Presence of large trees and tree diversity enhances carbon storage in the Western Ghats - Nasla Najeeb; Karun Jose; K.A. Sreejith; Sandeep Pulla; H.S. Suresh; Jayashree Ratnam; H.V. Raghavendra; Dayani Chakravarthy; Rajiv Kumar Chaturvedi (Biological Conservation, 2025)

Mapping of understorey invasive plant species clusters of Lantana camara and Chromolaena odorata using airborne hyperspectral remote sensing - Bodi Surya Pratap Chandra Kishore; Amit Kumar; Purabi Saikia; Nikhil Lele; Parul Srivastava; Sandeep Pulla; Hebbalalu Suresh; Bimal Kumar Bhattarcharya; Mohammed Latif Khan; Raman Sukumar (Advances in Space Research, 2024)

Plant dynamics in a tropical dry forest are strongly associated with climate and fire and weakly associated with stabilizing neighborhood effects - Sandeep Pulla; Hebbalalu Suresh; Handanakere Dattaraja; Raman Sukumar (Oecologia, 2021)

Multidimensional tree niches in a tropical dry forest - Sandeep Pulla; Hebbalalu S. Suresh; Handanakere S. Dattaraja; Raman Sukumar (Ecology, 2017)
The extent to which interspecific niche differences structure plant communities is highly debated, with extreme viewpoints ranging from fine‐scaled niche partitioning, where every species in the community is specialized to a distinct niche, to neutrality, where species have no niche or fitness differences. However, there exists a default position wherein niches of species in a community are determined by their evolutionary and biogeographic histories, irrespective of other species within the community. According to this viewpoint, a broad range of pair‐wise niche overlaps—from completely overlapping to completely distinct—are expected in any community without the need to invoke interspecific interactions. We develop a method that can test for both habitat associations and niche differences along an arbitrary number of spatial and temporal niche dimensions and apply it to a 24‐yr data set of the eight dominant woody‐plant species (representing 84% and 76% of total community abundance and basal area, respectively) from a 50‐ha permanent plot in a southern Indian tropical dry forest, using edaphic, topographic, and precipitation variables as niche axes. Species separated into two broad groups in niche space—one consisting of three canopy species and the other of a canopy species and four understory species—along axes that corresponded mainly to variation in soil P, Al and a topographic index of wetness. Species within groups tended to have significantly greater niche overlap than expected by chance. Community‐wide niche overlap in spatial and temporal niche axes was never smaller than expected by chance. Species‐habitat associations were neither necessary nor sufficient preconditions for niche differences to be present. Our results suggest that this tropical dry‐forest community consists of several tree species with broadly overlapping niches, and where significant niche differences do exist, they are not readily interpretable as evidence for niche differentiation. We argue, based on a survey of the literature, that many of the observed niche differences in tropical forests are more parsimoniously viewed as autecological differences between species that exist independently of interspecific interactions.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.